Analisis Akurasi Model Prediksi Financial Distress Perusahaan Properti dan Real Estat BEI 2021–2024 - Dozen, Wily; Tannia, Tannia (Business Management Journal, 2026)
This study examines the possibility of financial hardship for Indonesian real estate and property firms due to the sector's poor performance, which is seen in its falling GDP contribution, inconsistent gains in the Residential Property Price Index with sales, and falling profits. The many widely used financial distress prediction models provide different results and varying levels of accuracy, making it unclear which model best fits the sector between 2021 and 2024. This study seeks to determine the best model among Altman, Grover, Zmijewski, and Springate for forecasting financial hardship. On the IDX, 92 listed businesses in the real estate and property sector were included in a sample of 69 firms using a quantitative-descriptive method with deliberate sampling. The information was analyzed using SPSS 27 and the Kruskal-Wallis one-way ANOVA. The accuracy of the models varied greatly; Springate's was 46.38%, Zmijewski's was 75.36%, Altman's was 76.81%, and Grover's was 82.61%. The Grover model is the most accurate and precise model that should be used as an early warning system to aid in making decisions that will help avert financial challenges.